Conductive Hydroxyethyl Cellulose/Soy Protein Isolate/Polyaniline Conduits for Enhancing Peripheral Nerve Regeneration via Electrical Stimulation - Wu, Ping; Zhao, Yanan; Chen, Feixiang; Xiao, Ao; Du, Qiaoyue; Dong, Qi; Ke, Meifang; Liang, Xiao; Zhou, Qing; Chen, Yun (Frontiers in Bioengineering and Biotechnology, 2020)
Nerve regeneration remains a challenge to the treatment of peripheral nerve injury. Electrical stimulation (ES) is an assistant treatment to enhance recovery from peripheral nerve injury. A conductive nerve guide conduit was prepared from hydroxyethyl cellulose (HEC)/soy protein isolate (SPI)/PANI sponge (HSPS) and then the HSPS conduits were used to repair 10 mm sciatic nerve injury in rat model with or without ES, using HSPS+brain-derived neurotrophic factor (BDNF) and autografts as controls. The nerve repairing capacities were evaluated by animal experiments of behavioristics, electrophysiology, toluidine blue staining, and transmission electron microscopy (TEM) in the regenerated nerves. The results revealed that the nerve regeneration efficiency of HSPS conduits with ES (HSPS+ES) group was the best among the conduit groups but slightly lower than that of autografts group. HSPS+ES group even exhibited notably increased in the BDNF expression of regenerated nerve tissues, which was also confirmed through in vitro experiments that exogenous BDNF could promote Schwann cells proliferation and MBP protein expression. As a result, this work provided a strategy to repair nerve defect using conductive HSPS as nerve guide conduit and using ES as an extrinsic physical cue to promote the expression of endogenous BDNF.